Impactos do agronegócio no Alto Pantanal : um estudo sobre a produção de soja para a exportação no município de Poconé – MT - Amorim, Wellington Santos de (2021)
The Pantanal Complex is considered one of the largest wetlands on the planet and is also a national heritage, a biosphere reserve and a natural heritage of humanity by the United Nations Educational, Scientific and Cultural Organization (UNESCO). In light of this, an initiative of the Agroana-Girau Settlement and the Small Producers Cooperative of the Agroana-Girau Settlement (Cooperangi) in the insertion of an agroforestry system is pioneer. The identification of technified production for landed monoculture, in the territory close to the settlement, leads to a search for a greater understanding of the possible impacts of this coexistence and what are the main differences and divergences between the two modes of production. In this sense, the main objective of this work is to present and discuss the scenarios of territorial, productive and land use pressures exerted by agribusiness in the county of Poconé - MT. In order to answer what is the level of expansion of agribusiness in the upper Pantanal and how is the difference between the agents inserted in region of Agricultural community Agroana-Girau in the county of Poconé - MT? To this end, a field research was carried out to collect information as well as related to research producers in the region, in addition to the collection of secondary data, being a qualitative and exploratory research. The main conclusion of the present work is linked to the results regarding the cultivation expansion process in the region, institutional absence and multidimensional overlapping. The areas destined for the production of soy, in the surroundings of the AgroanaGirau settlement range from 50 to 700 hectares, totaling approximately 2900 hectares. With the proximity of the Agrofor. Syst. (Agroforestry Systems), this set of areas surrounds a production dedicated to community activity and given the objective of a less aggressive production without the use of pesticides, this is a sign that there may be relevant transformations taking place in this region. The level of expansion of agribusiness in the upper Pantanal is solid in the region with structured commercialization and agents cooperating for its commercialization. The expansion areas are growing solid and growing, marked mainly by the globalization of products, while there are no apparent institutional obstacles. The Agroana-Girau community, a pioneer in agroecological and organic production in the lowland region of Cuiabá, is in the middle of this expansion, where areas within a radius of at least 10 miles producing soybeans have been identified. What can direct and impact directly or indirectly the production of Agrofor. Syst. that aim at organic production. In the settlement, low income from land, low human capital combined with compatibility difficulties and institutional difficulties in accessing subsidies and assistance generate a cycle of production-to-place obstacles that make access to markets and the connection through use more difficult. from the earth.